Filamentous Fungi Isolates of Contaminated Sediment in the Amazon Region with the Potential for Benzo(a)pyrene Degradation - de Lima Souza, Hilton Marcelo; Sette, Lara Durães [UNESP]; da Mota, Adolfo José; do Nascimento Neto, Joaquim Ferreira; Rodrigues, André [UNESP]; de Oliveira, Tássio Brito [UNESP]; de Oliveira, Fernando Mendes; de Oliveira, Luiz Antônio; dos Santos Barroso, Hileia; Zanotto, Sandra Patricia (Springer Nature, 2016)
Filamentous fungi were isolated from contaminated sediment samples in the Amazon region of Brazil to select species with potential for benzo(a)pyrene (BaP) degradation, a polycyclic aromatic hydrocarbon (PAH) with high molecular weight and known for its mutagenic and carcinogenic properties. The isolates were submitted to biodegradability test using 2.6-dichlorophenol indophenol (DCPIP), gallic acid reaction, and evaluation of BaP influence in the enzymatic (ligninolytic) activity. The selected fungi were submitted to the taxonomic identification and used in biodegradation assays, which were carried out using gas chromatography coupled to mass spectrometry (GC-MS). A qualitative analysis of the presence of BaP metabolites that have recently been reported in literature was also performed by GC-MS. A total of 146 fungal isolates were recovered. Among them, 63.7 % were positive for the redox indicator DCPIP. From these isolates, 22.6 % showed positive responses to the gallic acid reaction. In enzymatic tests, the fungi Megasporoporia sp. S47 and unidentified Sordariales S69 presented highest activities of laccase and manganese peroxidase in the presence of BaP. Additionally, the white-rot fungus Megasporoporia sp. S47 showed better performance in BaP degradation (54 %). Therefore, Megasporoporia sp. S47, obtained from an environment with considerable PAH contamination, was selected as a promising genetic resource for application in new studies related to enzyme production and characterization and BaP degradation optimization.
Keywords: Benzo(a)pyrene; Biodegradation; Fungi; Ligninolytic enzymes; Polycyclic aromatic hydrocarbons